Analytical methods for food and dairy powders - Schuck, Pierre; Dolivet, Anne (Wiley-Blackwell, 2012)
Food and dairy powders are created by dehydrating perishable produce, such as milk, eggs, fruit and meat, in order to extend their shelf life and stabilise them for storage or transport. These powders are in high demand for use as ingredients and as food products in their own right, and are of great economic importance to the food and dairy industry worldwide. Today, the ability to control food and dairy powder quality is a source of key competitive advantage. By varying the dehydration process design, and by controlling the technological and thermodynamic parameters during dehydration, it is